L'infermiere e la percezione del Moral Distress nella cura del fine vita nel paziente dializzato - Elena Brioni; Nadia Pennacchio; Giulia Villa; Noemi Giannetta; Cristiano Magnaghi; Giuseppe Vezzoli; Duilio Fiorenzo Manara (AboutScience Srl, 2022)
The phenomenon of Moral Distress in nursing practice is described as a situation of suffering that arises when the nurse recognizes the ethically appropriate action to be taken and yet institutional impediments make it impossible for him to follow the right course of action. Dialysis patients often have a complex disease trajectory that sometimes involves professional and emotional challenges for staff, especially at the end of life. The objective of this review is to identify which strategies are useful for preserving emotional integrity and awareness in operational settings, for the benefit of both operators and patients.